RAISING QUESTIONS ABOUT THE APPOINTMENT OF CUSTOMS EXPERTISE IN ORDER TO CONTROL THE CORRECT CLASSIFICATION OF GOODS UNDER HS - SAPOZHNYK, Dmytro; PELYK, Lesia (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article considers the importance of the quality of questioning when appointing a customs examination, the procedure and rules for posing such questions, assessing their correctness, shows the algorithm for the correct formulation of the question regarding the appointment of a customs examination. The necessity of updating the methodological recommendations for posing questions to the expert is emphasized, since even the best methodological recommendations are useless if they are not applied in practice. Based on this, the expediency of introducing an appropriate training course and training for customs officials authorized to appoint commodity customs examinations and studies, in particular in the field of valuation of intellectual property, is shown. It is shown that when appointing a customs examination by a customs official, the expert should be assigned a specific task and set the range and content of issues on which the examination should be carried out. At the same time, it is not allowed to raise questions: that go beyond the competence of the expert (this may be grounds for refusal to conduct an examination); for the explanation of which no special expert knowledge is required; are of a legal nature; which may relate to the object of study due to its properties. The algorithm and the sequence of raising the question regarding the appointment of a customs examination, which allows to assess its correctness in accordance with the criteria established by law, which contain a prohibition on the absence of a certain (clear) semantic content in the question, or possible ambiguity (the possibility of interpretation) of the essence of the question, are analyzed. The necessity of formulating qualitative questions in compliance with the theory of their formulation and taking into account the specifics of the questions, taking into account the grounds for their occurrence, as well as the nature of the information the absence of which is indicated by the question (the so-called "whether-question" and "what-question") is proved. The conclusion is made that in order to prevent problems in the interaction of customs authorities and expert institutions in the process of organizing and conducting customs examinations, it is important to take into account the peculiarities of questioning when appointing examinations and to comply with the rules for asking questions to the expert.